Anticlastogenic effect of crude fucoidan extracts from Philippine sargassum species using in vivo bone marrow micronucleus assay - Amposta, Jamie Ysabel V.; Baluyan, Maria Zelina C. (2009)
This study investigated the anticlastogenic effect of two fucoidan preparations from Philippine Sagassum spp. using an vivo micronucleus assay in Mus musculus. Clastogenicity was induced using a single intraperitoneal dosage of 300 mg phenol per kilogram body weight. Mice were treated for 48 hours to compare the efficacy of the two fucoidan preparations namely, water extract and ethanol extract. Results showed phenol-induced clastogenecity in erythrocytes with percent PCE of 39.09%. Significant difference in percentage PCE of phenol exposed group to unexposed group (p<0.0001) was also detected. All mice groups showed no significant variation in dose responses to phenol (p=0.05). No significant variation was observed in mice exposed to the two fucoidan preparation in reducing percentage PCE(p=0.05). Mice treated by both fucoidan preparations showed significantly reduced % of PCEs as compared with positive control group (p=0.05). Thus, fucoidan extracted from Sargassum spp. may be an effective anticlastogenic agent exhibited by the reduced number of micronuclei by the in vivo micronucleus test. Fucoidan may act as putative anti-cancer treatment, specifically for leukemia -- Author's abstract.